Age-related Activation of Cyclic GMP–AMP synthase–Stimulator of Interferon Genes Signaling in the Auditory System is Associated with Presbycusis in C57BL/6J Male Mice. (15th January 2022) - Liu, Jinlan; Chen, Huiying; Lin, Xiaoyu; Yi, Jianqi; Ye, Wanli; Wei, Fangyu; Zhu, Xiaoting; Huang, Jialin; Su, Jiping
Highlights: Cytosolic mtDNA increased in aging auditory pathway. cGAS-STING activation in presbycusis. Inflammatory responses increased in the aged auditory system. Abstract: Presbycusis, or age-related hearing loss (ARHL), is primarily associated with sensory or transduction nerve cell degeneration in the peripheral and/or central auditory systems. During aging, the auditory system shows mitochondrial dysfunction and increased inflammatory responses. Mitochondrial dysfunction promotes leakage of mitochondrial DNA (mtDNA) into the cytosol, which activates the cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) pathway to induce type I interferon and inflammatory responses. However, whether this pathway is involved in the occurrence and development of ARHL is unknown. This study aimed to determine whether there are age-related changes in the levels of cytosolic mtDNA and cGAS–STING pathway activation in the auditory pathway and to explore their relationship with ARHL. The results showed that cGAS-positive immunoreactive cells were observed in the cochlea, inferior colliculus, and auditory cortex. Levels of cytosolic mtDNA, cGAS, STING, phosphorylated interferon regulatory factor 3, and cytokines were significantly increased in the cochlea, inferior colliculus, and auditory cortex of 6-, 9-, and 12-month-old mice compared with 3-month-old mice. These findings suggested that cytosolic mtDNA may play an important role in the pathogenesis of ARHL by activating cGAS–STING-mediated type I interferon and inflammatory responses.